In search of a meaningful classification for Amazonian marmosets: Should dwarf marmosets be considered Mico congenerics?. (2nd February 2018) - Silva, Felipe E.; Costa‐Araújo, Rodrigo; Boubli, Jean P.; Santana, Marcelo I.; Franco, Caetano L. B.; Bertuol, Fabrício; Nunes, Hermano; de Souza Silva‐Júnior, José; Farias, Izeni; Hrbek, Tomas
Abstract : The criteria to classify the diversity of Neotropical Primates have recently taken the discussion boards due to the reappraisal on the phylogenetic relationship of some groups. Such controversial and arbitrary decisions, however, can hamper conservation actions in as much as it becomes difficult to prioritise and set meaningful targets. It is the case for dwarf marmosets from central Amazonia. Today, the classification of dwarf marmosets in Mico or Callibella genus has not been satisfactorily settled. Aiming to contribute to the taxonomic and conservation assessment of dwarf marmosets, we conducted new data collection during 3‐year fieldwork in the Aripuanã River, where the species was discovered. We present the first phylogenomic analysis of the evolutionary relationships between marmosets, new data from mitochondrial DNA and morphology, as well new records to clarify geographic distribution. With this new evidence, we support dwarf marmosets as the genus Callibella . We further discuss the implications for the conservation of this marmoset.